Current Prognostic and Predictive Biomarkers for Endometrial Cancer in Clinical Practice: Recommendations/Proposal from the Italian Study Group - Zannoni, Gian Franco; Bragantini, Emma; Castiglione, Francesca; Fassan, Matteo; Troncone, Giancarlo; Inzani, Frediano; Pesci, Anna; Santoro, Angela; Fraggetta, Filippo (Frontiers in Oncology, 2022)
Endometrial carcinoma (EC) is the most common gynecological malignant disease in high income countries, such as Europe and the USA. The 2020 edition of the World Health Organization Classification (WHO) of Tumours of the Female Genital Tract underlines the important clinical implications of the proposed new histomolecular classification system for ECs. In view of the substantial genetic and morphological heterogeneity in ECs, both classical pathological parameters and molecular classifiers have to be integrated in pathology report. This review will focus on the most commonly adopted immunohistochemical and molecular biomarkers in daily clinical characterization of EC, referring to the most recent published recommendations, guidelines and expert opinions.